PENGARUH BRAND AWARENESS, BRAND IMAGE, DAN WORD OF MOUTH TERHADAP MINAT PEMBELIAN ULANG KONSUMEN MIE GACOAN YOGYAKARTA - Rae Ginola Purba; Rudy Badrudin (LPPM STIE YKPN Yogyakarta, 2025)
This study aims to analyze the influence of brand awareness, brand image, and word of mouth on the repurchase intention of Mie Gacoan consumers in Yogyakarta. The approach used is quantitative, with data collected in the form of numbers to analyze the relationships between the variables under study. The research population consists of all Mie Gacoan consumers in Yogyakarta, and the sample is taken using purposive sampling techniques, with criteria for consumers who reside in Yogyakarta and have purchased Mie Gacoan at least once. The data collection technique uses a Likert scale 5-point questionnaire to assess respondents' perceptions of the variables under study. The results of hypothesis testing analysis show that brand awareness, brand image, and word of mouth have an impact on the repurchase intention of Mie Gacoan consumers in Yogyakarta.